Growth Analysis of Mixed Ancestry Infants Aged 0 – 18 months, South Africa - Arendse, Liesl (Department of Human Biology, 2023)
Early life nutritional status and subsequent growth trajectory may impact adult health status later in life. In South Africa, children of mixed ancestry (MA, 1-10 years) have a significantly higher risk for stunting (according to WHO growth standards) compared to other population groups. Adults of MA have the second highest type II diabetes mellitus prevalence, and hypertension doubled between 2008-2016. Insight into healthy MA infant growth may help to explain, in part, this pattern of adult-onset NCDs. This study aimed to document healthy MA infant growth, against the WHO growth standards, in a 0 – 18-month-old cohort. Regression analyses were used to investigate which socio-demographic and/or socio-economic factors related to age-standardised growth. Recruited dyad pairs from three clinics (two public, one private) included 161 infants (boys=71, girls=90), divided into three six-month age groups. Standard nutritional anthropometry was conducted. Statistical associations between age-standardised z-scores with socio-demographic and socio-economic factors (recorded via questionnaires) were assessed, and subsequently used in regression modelling of age-standardised growth. Infants under 6 months grouped between -2 SD and +1 SD for length, weight, and head circumference WHO z-scores; those over 6 months grouped between -1 SD and +2SD. Stunting was more prevalent in infants under six months, and overweight for infants over six months, with a higher prevalence in boys, including wasting. Stunting prevalence in this cohort was under 3%, much lower than the national prevalence reported as 27.5% (<5 years). Conversely, more than 6% were overweight/obese, similar to previous national prevalence (<5 years). Positive significant contributors in regression models were maternal age and education for age-standardised length, weight, and head circumference; gestational age for length and head circumference; exclusive breastfeeding duration for head circumference only; household occupancy and age complementary foods were introduced, for length and weight; explaining some growth trajectory variance within this cohort. Although most of these infants fell within the WHO growth standard norm, the negative age-standardised results for infants under six months may explain overweight/obesity prevalence in those over six months. This research contributes to the knowledge of populational growth differences of healthy full-term infants that may inform the aetiology of adult-onset NCDs.